The Sanfengshan copper deposit and early Carboniferous volcanogenic massive sulfide mineralization in the Beishan orogenic belt, Northwestern China. (March 2018) - Wang, Jialin; Gu, Xuexiang; Zhang, Yongmei; Zhou, Chao; He, Ge; Liu, Ruiping
Highlights: We report for the first time a volcanogenic massive sulfide deposit in the Beishan orogenic belt. Early Carboniferous sulfide mineralization occurs in basalts at Sanfengshan. The hosting basalts were formed in a fore-arc setting. The copper deposit is syngenetic in origin. Abstract: The Sanfengshan copper deposit, located in the Beishan orogenic belt, Northwestern China, is hosted in the lower member of the Hongliuyuan Formation, an early Carboniferous metavolcanic-sedimentary sequence. Mineralization occurs as stratiform, stratiform-like and lenticular orebodies, and comprises of laminated, brecciated, banded, massive, and disseminated ores. The mineralogy is dominated by pyrite, chalcopyrite and sphalerite. Fe-Mn chert is widely distributed and generally occurs as massive, laminated, bands or lenses, which are consistent with the orebody. Alteration at Sanfengshan displays a clear concentric zoning pattern and the footwall alteration is more intense and somewhat thicker than the hanging-wall alteration. Systematic geochemical investigation on the volcanic rocks in this area shows that the basalts of the Hongliuyuan Formation (HLY) are predominantly tholeiites with nearly flat rare earth element (REE) pattern, insignificant negative anomalies of high field strength elements (HFSEs), and low Ti/V and Th/Nb ratios. They were most likely derived from partial melting of depleted asthenospheric mantle and formed in a fore-arc setting during initiation of the southward subduction of the Paleo-Asian Ocean. The basalts of the Maotoushan Formation (MTS) display a calc-alkaline nature and are enriched in large ion lithophile elements (LILEs) and depleted in HFSEs, suggesting an active continental margin setting. Sulfur isotope (δ 34 S) values of the sulfide and sulfate minerals vary between 0‰ and 5.4‰, which are consistent with sulfur derivation from leaching of the host volcanic rocks, although a direct magmatic contribution cannot be ruled out. The Re-Os isotope data of pyrite yield an isochron age of 353 ± 35 Ma, consistent with the age of the host HLY basalts. Thus, a syngenetic (volcanogenic massive sulfide) model is proposed and it is concluded that the Sanfengshan copper deposit is a typical Cyprus-type VMS deposit that formed in an early Carboniferous fore-arc setting in the Beishan orogenic belt.